2015
DOI: 10.20966/chn.2015.48.340
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vojta stimulation in psychomotor development of children with Down syndrome

Abstract: STRESZCZENIECel pracy. Celem podjętych badań było dokonanie analizy rozwoju psychoruchowego dzieci z zespołem Downa systematycznie stymulowanych metodą Vojty, zarówno w warunkach domowych, jak i w Poradni Rehabilitacji przy UDSK w Białym-stoku przez terapeutę oraz porównanie uzyskanych wyników z grupą dzieci z zespołem Downa, które były sporadycznie stymulowane metodą Vojty. Materiał i metody. Badania przeprowadzono na grupie 45 dzieci z zespołem Downa w wieku od 18. do 24. miesiąca życia. W celu oceny rozwoju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Indeed, previous literature showed that preterm and or low birth weight children showed alterations in language, social-emotional, and neuro-psychological profiles when compared to children with higher weight and closer to 37 weeks of gestational age [8,9] . The preterm birth was related with a six times or more higher risk of DlD [10,11] . Luu et al, 2009 reported that preterm children with and without brain injury required more support at reading, writing, and mathematics, as well as they had more behavioral issues [12] .…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, previous literature showed that preterm and or low birth weight children showed alterations in language, social-emotional, and neuro-psychological profiles when compared to children with higher weight and closer to 37 weeks of gestational age [8,9] . The preterm birth was related with a six times or more higher risk of DlD [10,11] . Luu et al, 2009 reported that preterm children with and without brain injury required more support at reading, writing, and mathematics, as well as they had more behavioral issues [12] .…”
Section: Discussionmentioning
confidence: 92%